Entrapment defence in Malaysia / A.H. Mohamad Zulkifli Abdul Hamid - A.H. Mohamad Zulkifli, Abdul Hamid (2004)
The fundamental principle und rlying the rim in l justice system in Malaysia is that an accused person is innocent until proven guilty by a competent court of law. In line with thi principle, the rimina\ justice system of Malaysia provides various safeguards to protect accused persons. However, covert policing methods, normally the use of informers and I or undercover police officers, raise profound issues as regards the fairness of trials. In Malaysia there is no rule that evidence obtained by the use of trickery and deception, even by provocation and entrapment be automatically excluded. It is necessary to appreciate that courts have a responsibility to protect the overall integrity of the criminal justice system. This must, therefore, inevitably mean that in setting standards of fairness, a court in a particular case must consider whether to condemn them by resort to its common law power to stay the proceedings or exclude the evidence. But, in cases which involved informer or agent provocateur, a distinction must be made to divide the line between a mere informer and a particeps criminis, that is the degree of the persons participation or a person who enticed another to commit crime. The focus at trial is on the conduct of the police irrespective of the culpability or predisposition of the accused. Potential benefits of this approach include the protection of the purity and integrity of the criminal justice system and the deterrence of police misconduct.